Plant foods consumed at the Neolithic site of Qujialing (ca. 5800-4200 BP) in Jianghan Plain of the middle catchment of Yangtze River, China - Khan, Muslim; Yao, Ling; Yang, Yuzhang; Tao, Yang; Li, Weiya; Zhang, Dewei; Luo, Yunbing; Zhang, Juzhong (Frontiers in Plant Science, 2022)
The site of Qujialing experienced a long, sustained process of the development of Neolithic culture in the Jianghan Plain, with a period of some1600 years. Our previous studies based on macrofossil remains and phytoliths revealed that rice (Oryza sativa) from Qujialing was already domesticated, and millet (Setaria italica and Panicum miliaceum) had also been spread into the site since the Youziling Culture period (5800-5100 BP). Nevertheless, no direct evidence has been provided regarding the daily consumed plant foods, especially plant foods obtained by gathering, throughout the site occupation. This paper thus examines pottery sherds (n=41) associated with culinary practices from Qujialing with starch grain analysis. Apart from starch grains from rice and millet, the results indicate that job’s tears (Coix lacryma-jobi), lotus roots (Nelumbo nucifera), tubers possibly from Chinese yam (Dioscorea panthainca), acorns (Quercus sp.), and beans (Vigna sp. or/and Vicia sp.) were consumed by the ancient Qujialing people, within job’s tears and lotus roots were not discovered before in the macrofossil remains and phytoliths. Combining the starch data and multiple lines of evidence from macrofossil remains and phytoliths, it is suggested that rice was among the most frequently consumed plant foods since the first occupation phase at Qujialing, while acorns could have been gradually replaced by other agricultural products (i.e., rice) and became less important food ingredients, especially when agriculture was more developed in the last occupation phase at Qujialing. These novel findings not only complement our previous research by providing the first line of evidence of paleodiet in the Jianghan Plain from the perspective of starch grain analysis but also delivers a better understanding of the characterized dietary trends and agricultural development in the research region.